2004
DOI: 10.1097/01.shk.0000131489.83194.1a
|View full text |Cite
|
Sign up to set email alerts
|

Survival in a Rat Model of Lethal Hemorrhagic Shock Is Prolonged Following Resuscitation With a Small Volume of a Solution Containing a Drag-Reducing Polymer Derived From Aloe Vera

Abstract: Drag-reducing polymers (DRP) increase tissue perfusion at constant driving pressure. We sought to evaluate the effects of small-volume resuscitation with a solution containing a DRP in a rat model of hemorrhage. Anesthetized rats were hemorrhaged at a constant rate over 25 min. In protocol A, total blood loss was 2.45 mL/100 g, whereas in protocol B, total blood loss was 3.15 mL/100 g. Five minutes after hemorrhage, the animals were resuscitated with 7 mL/kg of either normal saline (NS) or NS containing 50 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
0
45
1
2
Order By: Relevance
“…These studies were originally motivated by the knowledge that small amounts of long-chain polymer additives-"drag-reducing polymers" (DRPs) -can dramatically reduce drag in turbulent flows while having negligible effect on laminar flows [94]. Studies with laboratory animals indicate that the addition of DRPs to blood leads to many beneficial effects, including (1) reduced atherosclerotic plaque deposition ( Figure 11.3(a)) [90,95]; (2) increased cardiac output [96] and reduced severity of cardiac stenosis or myocardial infarction [97][98][99][100]; (3) improved survival probability after severe hemorrhage with use of polymer-containing resuscitation fluids [91,93,101] (see Fig. 11.3(b)); (4) reduced immune attack of implanted polymeric tissue scaffolds [92] (see Fig.…”
Section: Effect Of Plasma Rheology On Cell Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were originally motivated by the knowledge that small amounts of long-chain polymer additives-"drag-reducing polymers" (DRPs) -can dramatically reduce drag in turbulent flows while having negligible effect on laminar flows [94]. Studies with laboratory animals indicate that the addition of DRPs to blood leads to many beneficial effects, including (1) reduced atherosclerotic plaque deposition ( Figure 11.3(a)) [90,95]; (2) increased cardiac output [96] and reduced severity of cardiac stenosis or myocardial infarction [97][98][99][100]; (3) improved survival probability after severe hemorrhage with use of polymer-containing resuscitation fluids [91,93,101] (see Fig. 11.3(b)); (4) reduced immune attack of implanted polymeric tissue scaffolds [92] (see Fig.…”
Section: Effect Of Plasma Rheology On Cell Distributionmentioning
confidence: 99%
“…Experiments in microfluidic devices [93,105] have shown that the addition of a small amount of DRPs to suspension of RBCs results in a redistribution of RBCs with a significant reduction in the [90]. (b) Survival vs. time for rats subjected to hemorrhage and not treated (CON), treated by injection of normal saline (NS) or intravenously injected with saline containing a drag-reducing polymer [91]. (c) Poly(L-lactate) tissue scaffolds recovered after 7 weeks of implantation in a rat.…”
Section: Effect Of Plasma Rheology On Cell Distributionmentioning
confidence: 99%
“…Attempts at explaining the mechanism of this effect by changes in blood rheology were not confirmed in experiments on viscosimeters [5][6][7], because numerous specific factors of functioning of a living microcirculatory bed (MCB) forming blood rheology could not be reproduced simultaneously [2]. The curve of velocity profiles reflects real value of shear rate in the stream, while its changes in the vessel indicate transformation of the bloodflow regimen and hence, qualitative changes in blood rheology.…”
mentioning
confidence: 99%
“…The development of methods for adequate evaluation of blood rheology acquired special significance in studies of the effects of surface-active substances on blood supply intensity under critical conditions caused by acute blood loss (hemorrhagic shock) [2,[5][6][7]. Attempts at explaining the mechanism of this effect by changes in blood rheology were not confirmed in experiments on viscosimeters [5][6][7], because numerous specific factors of functioning of a living microcirculatory bed (MCB) forming blood rheology could not be reproduced simultaneously [2].…”
mentioning
confidence: 99%
“…Marcias CA. group concluded that resuscitation with a small volume of DRP prolongs survival in rats with lethal hemorrhagic shock [11] . Sixteen adult male rats were anaesthetized and mechanically ventilated.…”
mentioning
confidence: 99%